Analisis penerapan SAK-ETAP pada perusahaan PT Lintas Samudra Jaya - Fatikha, Khusnul; Husna, Gempita Asmaul (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Financial statements are the main means of communicating information to parties who need both internal and external companies, which contain the results of the accounting process that can be used as a communication tool between financial data and activities of a company and parties with an interest in data or activities of a company. In this case, the company PT Lintas Samudra Jaya as the destination entity that publishes financial reports to the public for external users is expected to be able to make financial reports that comply with the standards, namely the financial accounting standards of entities without public accountability (SAK ETAP). The purpose of this study was to determine the use of financial statements based on the financial accounting standards of entities without public accountability (SAK ETAP), as well as the obstacles faced in its implementation. This research uses qualitative research with case study method. the steps taken to obtain data and information are interviews and documentation. The results in this study indicate that the financial statements prepared by PT Lintas Samudra Jaya have not implemented financial accounting standards for entities without public accountability (SAK ETAP) in this regard due to limited knowledge and human resources.